Complex use of cycleand power-ergometry in determining the physical working capacity of young athletes - Khoroshukha, M. F.; Filippov, M. M.; Bosenko, A. I.; Mykhaliuk, Ye. L.; Buriak, O. Yu. (Modern medical technology, 2023)
The aim of this study is to scientifically substantiate the possibilities of complex use of cycle- and power-ergometry in determining aerobic and anaerobic-aerobic performance of power nature. Materials and methods. Young athletes (boys) aged 15–16 (n = 91) of the Brovary Higher School of Physical Education (Kyiv region) (experimental group), who participated in the study, were divided into two groups. Group А (n = 47) – speed-power sports (boxing, freestyle wrestling); group B (n = 44) – endurance sports (track and field athletics: 800, 1500, 3000 and 5000-meters race, bicycle racing 50 and 75 km). Sports experience was 3–5 years and more. The control group (group К) consisted of students aged 15–16, who did not play sports (n = 25). Physical working capacity was determined using two methods: submaximal cycle ergometric test PWC170 and submaximal power ergometric test PWC170. Method of power ergometry (patent of Ukraine No 49417) has no analogues in countries of near and far abroad. Results. The fact of the specific influence of different kinds of dosed physical exercises (strength and power exercises) on PWC170 indicators was established. Thus, no probable differences in aerobic performance indicators were found in wrestlers and boxers during the cycle ergometric test. And conversely, under the conditions of power ergometric testing, we find a significant increase in their PWC170 indicators in relation to athletes of endurance sports. The opposite character of changes was observed when testing the track and field athletes and bike riders. According to the results of the conducted cycle ergometry, these athletes had a significant increase in aerobic performance indicators in comparison with the athletes of speed-power sports. However, the changes of anaerobic-aerobic performance were not significant. It was observed that the adolescents, who did not play sports, had statistically insignificant changes in PWC170 indicators both in the conditions of cycle ergometric and power ergometric testing. Conclusions. The fact of specific influence of different types of training exercises on the body functions of adolescents was confirmed. The possibility of introducing the methods of complex use of aerobic (cycle ergometry) and anaerobic-aerobic loads (power-ergometry) into the practice of medico-biological control of young athletes is shown. Diagnostics of various types of physical working capacity (PWC170) will provide the coach with operational information about the functional state of the athletes’ body, which will allow to effectively manage a training process.